Interactions between three common subunits of yeast RNA polymerases I and III. - Lalo, D (1993)
The AC40 and AC19 subunits (encoded by RPC40 and RPC19) are shared by yeast RNA polymerases I and III and have a local sequence similarity to prokaryotic alpha subunits. Mutational analysis of the corresponding "alpha motif" indicated that its integrity is essential on AC40 subunit but is not essential on AC19 subunit. By applying the two-hybrid method, these two polypeptides were shown to associate in vivo. Extragenic suppression of rpc19 and rpc40 mutations confirmed that AC19 and AC40 subunits interact with each other in vivo and revealed an interaction with ABC10 beta subunit [encoded by RPB10; Woychick, N. A. & Young, R.A. (1990) J. Biol. Chem. 265, 17816-17819], one of the five polypeptides common to all three nuclear RNA polymerases. A correction of the RPB10 sequence showed that ABC10 beta subunit is a 70-amino acid polypeptide, as confirmed by peptide microsequencing. These results suggest that the assembly of RNA polymerase I and III requires the association of ABC10 beta subunit with an AC19/AC40 heterodimer.